Factors associated with the duration of breastfeeding in children under 2 years of age in Peru 2021-2022 - Zorrilla Cabrejo, Mirella; Espinoza Rojas, Rubén Espinoza Rojas (Medicina Clínica y Social, 2024)
Introduction: The duration of breastfeeding is crucial for child health; however, the prevalence has decreased in recent years, placing children in a population at risk. Objective: To determine the factors associated with the duration of breastfeeding in children under 2 years of age in Peru 2021-2022. Methodology: Cross-sectional analytical study, through the secondary analysis of data from the Demographic and Family Health Survey (ENDES) of 2021 and 2022. The sample size was 4951 children with their respective mothers. Infant and maternal factors were evaluated using the F-statistic corrected for bivariate analysis with a statistical significance of p
Keywords: Breastfeeding; children; Infant Formula; Kangaroo-Mother Care Method; Maternal Age